2019
DOI: 10.1504/ijor.2019.096940
|View full text |Cite
|
Sign up to set email alerts
|

Modelling a bi-objective airport gate scheduling with controllable processing time using hybrid NSGA-II and VNS algorithm

Abstract: In this research, we address a bi-objective model in a more realistic situation such that airport gate processing time is controllable. It is assumed that the possible compression/expansion processing time of a flight can be continuously controlled. The aim is simultaneously: 1) minimise the total cost of tardiness, earliness, delay and compression as well as expansion costs of job processing time; 2) minimise the passengers overcrowding on gate. In this study, a mixed-integer programming model is proposed. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Planes are diverted to an apron if they are unable to be allocated to a gateway because of overlaps. In addition, in a more realistic setting where airport gate processing time is controllable, Khatibi et al ( 2019 ) suggested a bi-objective framework to lower the overall impact of task processing time expansion, unavailability, earliness, latency, and compression. The project also seeks to reduce the number of passengers crowded onto gates.…”
Section: Related Workmentioning
confidence: 99%
“…Planes are diverted to an apron if they are unable to be allocated to a gateway because of overlaps. In addition, in a more realistic setting where airport gate processing time is controllable, Khatibi et al ( 2019 ) suggested a bi-objective framework to lower the overall impact of task processing time expansion, unavailability, earliness, latency, and compression. The project also seeks to reduce the number of passengers crowded onto gates.…”
Section: Related Workmentioning
confidence: 99%